Stock market growth in Ghana: Do financial sector reforms matter? - Kofi Kamasa; Linda Owusu; Grace Nkansah Asante (Cogent Business & Management)
Owing to the significant role of financial sector reforms in economic growth, several studies have examined its transmission channels. This paper focuses on the stock market channel by investigating the impact of financial sector reforms on stock market growth in Ghana from 1990 to 2019. A multidimensional index was constructed to measure the financial sector reforms. Employing fully modified least squares (FMOLS) and error-correction models, the findings reveal that financial sector reforms promote stock market growth in Ghana in the long run. By disaggregating the financial sector reforms, the findings reveal that competitive reform has the highest impact followed by behavioural and privatisation reforms respectively. Finally, the findings reveal a bi-causal relationship between financial sector reforms and stock market growth. The paper thus implores the Securities and Exchange Commission (SEC) to reinforce its supervisory role, policy implementation, and investor protection laws to ensure greater compliance with the reforms. In addition, macroeconomic policies that are helpful to the growth of the capital market must be deepened to stimulate expected growth in the Ghanaian stock market.